2005
DOI: 10.1074/jbc.m506753200
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Merozoite Surface Protein 3, a Representative of a Family of Plasmodium falciparum Surface Proteins, Reveals an Oligomeric and Highly Elongated Molecule

Abstract: Vaccination with the merozoite surface protein 3 (MSP3) of Plasmodium falciparum protects against infection in primates and is under development as a vaccine against malaria in humans. MSP3 is secreted and associates with the parasite membrane but lacks a predicted transmembrane domain or a glycosylphosphatidylinositol anchor. Its role in the invasion of red blood cells is unclear. To study MSP3, we produced recombinant full-length protein and found by size exclusion chromatography that the apparent size of MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
47
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 37 publications
8
47
0
2
Order By: Relevance
“…Coloring of the electrostatic potential is from red (Ϫ15 kJ mol Ϫ1 ), through white (0 kJ mol it remains possible that dimerization is still required for ligand recognition. In the full-length protein, dimerization is probably facilitated by the C-terminal SPAM domain present in both PfMSPDBL1 and -2, as is the case for MSP3 (46). Dimerization via this motif would likely orient two DBL domains in a parallel fashion; however, flexibility within the linker region between the DBL and SPAM domains may allow for a variety of DBL dimer interfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coloring of the electrostatic potential is from red (Ϫ15 kJ mol Ϫ1 ), through white (0 kJ mol it remains possible that dimerization is still required for ligand recognition. In the full-length protein, dimerization is probably facilitated by the C-terminal SPAM domain present in both PfMSPDBL1 and -2, as is the case for MSP3 (46). Dimerization via this motif would likely orient two DBL domains in a parallel fashion; however, flexibility within the linker region between the DBL and SPAM domains may allow for a variety of DBL dimer interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The leucine zipper-like region has been shown to be responsible for oligomerization of MSP3. Analysis of the physical properties of MSP3 has suggested that it forms a highly extended and oligomeric structure on the merozoite surface that would allow it to interact with the red blood cell at relatively long distances (46), most notably, dimerization of MPS3 is solely through the leucine zipper-like domain. As PfMSPDBL1 and -2 bind red blood cells through the DBL domains and share with MSP3 a SPAM domain at the C terminus, they are also likely to be long extended molecules able to bind to their specific receptors.…”
Section: Discussionmentioning
confidence: 99%
“…A vaccine based on MSP3 N-terminal fragment is already in human trials (9,10). In addition to being a potential vaccine candidate, two other characteristics of MSP3 stand out as follows: first, MSP3, although a soluble protein, forms oligomers, and second, it can bind to heme, although the significance of these characteristics is not well understood (7,11).…”
mentioning
confidence: 99%
“…Other surface proteins, including MSP3, MSP6, MSP7, and MSP9 (also known as ABRA), are soluble proteins and are present on the merozoite surface as a protein complex, possibly through protein-protein interactions (4). Of these proteins, MSP3 is of particular interest, both as a vaccine candidate antigen as well as for its peculiar structural characteristics (5)(6)(7).…”
mentioning
confidence: 99%
“…MSP-6 is related to MSP-3 (3) based on a high sequence similarity at the C terminus, which can give rise to antibodies reacting with both proteins (10,11). Recently, it has been shown that MSP-3 can form highly elongated dimers and tetramers via its C terminus containing a predicted coiled-coil region (12).…”
mentioning
confidence: 99%